TASKS OF DISTANCE LEARNING IN HIGHER EDUCATION INSTITUTIONS AND PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF ITS ORGANIZATION - Khakimova Yo. T. (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the tasks of distance learning in higher education institutions, educational process management systems and pedagogical, psychological, didactic and social aspects of the organization of distance learning.